An object of beauty [compact disc, unabridged] - Martin, Steve, 1945- (Hachette Audio, 2010)
Lacey Yeager is an aspiring artist who dreams of making it big in New York City. Over the course of 20 years, she climbs the rungs of NYC's art scene, charming those she meets with her energetic personality. Although her career soars to new heights, Lacey discovers that the life of an artist isn't as glamorous as she once thought.